PROSEDUR PERENCANAAN DAN ANGGARAN KANTOR KESYAHBANDARAN UTAMA TANJUNG PRIOK – JAKARTA UTARA - Albert M.E Wijaya Wijaya; Emerald G.M. Tobing (Fakultas Ekonomi Universitas Kristen Indonesia, 2018)
Any company or organization that is established must have a goal to be achieved by effective and efficient manner. It also applies to all organizations jenisi state as engaged in the political field, the economic field, the field of Business, Social and Cultural field - like Pendidikam and Health - a nonprofit organization, Society of Social Institutions and Religious environment even though. Economic development is carried out by a country always followed by the development aspect that continues to increase rapidly and rumit.Seiring with these developments, the various efforts undertaken by any institution or company to improve its performance. In an agency for planning and budgeting becomes important to achieve the goals and objectives of effective and efficient so as to produce the expected absorption or improve performance to be achieved. However, the planning and budget there are some problems encountered. As Realization / Biodegradable DIPA 2015 budget year. House of Representatives (DPR) to understand the proposed Budget Ceiling MoT for 2015 amounted Rp.51,605,867,000 but what happens during the running of the fiscal year 2015 there were problems experienced in personnel expenditure report with a shortage fee. The results of the practice of field work carried out showed that the procedures of planning and budget at the main kesyahbandaran office still need to be evaluated to support the performance of the office as a public service.Keywords: Planning, Procedure, Budget